Mycophenolate mofetil‐induced peripheral neuropathy in the treatment of membranous glomerulonephropathy: A case report. Issue 12 (13th December 2021) - Moghimi, Minoo; Nekoukar, Zahra; Gholami, Farhad
Abstract: Mycophenolate mofetil (MMF) as an immunosuppressive agent is widely used in the management of Membranous Glomerulonephropathy (MGN). In this report, we described a 66‐year‐old male MGN case treated with MMF and revealed acquired sensory‐motor axonal polyneuropathy, which is rare and has not been reported before. Abstract : Although mycophenolate mofetil is effective in the management of some immune‐mediated neuromuscular disorders, it could inversely cause peripheral neuropathy as a rare side effect, which is hopefully reversible with drug discontinuation.